Pemikiran visual terhadap permainan ceper berasaskan sistem sosial budaya / Zulpaimin Hamid dan Abdul Halim Hussain - Hamid, Zulpaimin; Hussain, Abdul Halim (2016)
This study deliberates the results of visual thinking of Ceper, a traditional game played by children in the village of Permatang Pasir, Bagan Samak, Bandar Baharu, Kedah Darul Aman based on methods, processes, equipment and materials for the game. The existence of the game is associated with the framework of the social and cultural system. The focus of this study is to detect, document, analyse and interpret the game of Ceper in natural surroundings. The review of the game attempts to discover patterns and symbols from the behaviour of players and the creator of game equipment which are interpreted as a form of expression of players‟ visual thinking. The form of expression from the visual thinking of players and the creator of game equipment is able to demonstrate educational values in children’s games. These are the values that support and act as a foundation of the child’s identity. This study is based on a qualitative approach to interdisciplinary paradigm. The case study used a variety of study designs. Data acquisition was made through observation, interviews, documents and visual recorders. Data were analysed using Miles and Huberman interactive model. Findings from this study indicate that the game of Ceper is closely linked to the conservation of values embraced by the surrounding community. These values are then absorbed into the players and the creator of game equipment through the intermediary of a system of symbols and patterns of behaviour. The values from the symbols and patterns are formed through a process of imitation of players‟ natural surroundings. The results of this study can be used by educators to place education and all educational activities on a cultural platform so that children will have strong adherence to the root of their cultural values.